Factors associated with objectively measured exercise participation after hospitalization for acute coronary syndrome. (15th January 2019) - Goodwin, Ashley M.; Duran, Andrea T.; Kronish, Ian M.; Moise, Nathalie; Sanchez, Gabriel J.; Garber, Carol Ewing; Schwartz, Joseph E.; Diaz, Keith M.
Abstract: Background: Guidelines recommend exercise for secondary prevention of acute coronary syndrome (ACS), however adherence to guidelines is low. A paucity of data examining factors associated with objectively-measured exercise post-discharge in ACS survivors exists. The purpose of this study was to identify factors associated with exercise during the 5 weeks after ACS discharge. Methods: A sample of 151 ACS patients treated at a university hospital were enrolled into an observational cohort study and wore an accelerometer for 35 days post-discharge. Days on which participants accumulated ≥30 min of moderate-to-vigorous physical activity in bouts ≥10 min were considered exercise days. Participants were categorized as non-exercisers (0 exercise days) or exercisers (≥1 exercise day). A multi-variable logistic regression model was used to examine the association between exercise and socio-demographics, depression, SF-12 physical and mental health scores, disease severity, length of hospitalization, and percutaneous coronary intervention. Results: 39.7% of participants were non-exercisers. Factors associated with non-exercise were age (OR: 1.11; 95% CI: 1.06–1.17, p < 0.001), female sex (OR: 2.76; 95% CI: 1.10–6.95, p = 0.031), and lower SF-12 physical health score (OR: 0.94; 95% CI: 0.90–0.98, p = 0.005). Conclusion: In ACS patients in whom exercise participation was objectively measured for 5 weeks post-discharge, demographic and poor physical health factors were associated with non-exercise. These findings identify populations (e.g. older adults, women) at especially high risk for being physically inactive in whom more intense intervention may be warranted. Highlights: A striking 40% of patients did not exercise a single day over 5 weeks post-ACS. Older age, female sex, and poor physical health were associated with non-exercise. Older adults and women may need robust intervention to promote exercise post-ACS.